2016
DOI: 10.1177/1074248416636477
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil, a Nitric Oxide Donor and ATP-Sensitive Potassium Channel Opener, Protects Against Dystrophin-Deficient Cardiomyopathy

Abstract: Background-Dystrophin-deficient cardiomyopathy is a growing clinical problem without targeted treatments. We investigated whether nicorandil promotes cardioprotection in human dystrophin-deficient induced pluripotent stem cell (iPSC)-derived cardiomyocytes and the muscular dystrophy mdx mouse heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 59 publications
(75 reference statements)
2
49
0
Order By: Relevance
“…iPSCs as disease models can be used to model intercellular communication between neighboring cell types in the heart by studying the effects of cell‐type–specific exosomes. Numerous studies have validated the use of iPSCs as a model system to study genetic cardiac diseases such as long QT syndrome, LEOPARD syndrome, and Duchenne muscular dystrophy . In addition, there is growing interest in using iPSC‐derived cells to study environmental modifiers of disease.…”
Section: Ipscs As a Tool To Understand Intercellular Communication Inmentioning
confidence: 99%
See 1 more Smart Citation
“…iPSCs as disease models can be used to model intercellular communication between neighboring cell types in the heart by studying the effects of cell‐type–specific exosomes. Numerous studies have validated the use of iPSCs as a model system to study genetic cardiac diseases such as long QT syndrome, LEOPARD syndrome, and Duchenne muscular dystrophy . In addition, there is growing interest in using iPSC‐derived cells to study environmental modifiers of disease.…”
Section: Ipscs As a Tool To Understand Intercellular Communication Inmentioning
confidence: 99%
“…Numerous studies have validated the use of iPSCs as a model system to study genetic cardiac diseases such as long QT syndrome, 27,93 LEOPARD syndrome, 94 and Duchenne muscular dystrophy. 29,95 In addition, there is growing interest in using iPSC-derived cells to study environmental modifiers of disease. The iPSC-derived cells can be exposed to various conditions to precipitate oxidative, metabolic, or endoplasmic reticular stress or subjected to neurohormones, growth factors, or hypoxia to mimic certain disease states.…”
Section: Ipscs As a Tool To Understand Intercellular Communication Inmentioning
confidence: 99%
“…The use of iPSC-CMs to model cardiomyopathic disease has more often been restricted to genetically inherited or spontaneous cardiomyopathies such as hypertrophic cardiomyopathy[43], Pompe’s disease [44], or Duchenne muscular dystrophy [40, 45]. Less commonly, iPSC-CMs are used to model acquired cardiomyopathies such as HFpEF.…”
Section: Patient-specific Ipsc-derived Cardiomyocytes To Study Genetimentioning
confidence: 99%
“…Since then, pharmacological studies showed that KATP openers exerted profound cardioprotective effects in numerous mammalian species (Afzal et al, 2016; Flagg et al, 2010; Gao et al, 2016; Grover & Garlid, 2000; Yamada et al, 2006; Zingman et al, 2002). Following the finding of the mitochondrial KATP that locating at the inner membrane of mitochondria in 1991 (Inoue et al, 1991), Garlid et al (1997) and Liu et al (1998) demonstrated it as a trigger of ischemic preconditioning.…”
Section: Introductionmentioning
confidence: 99%